Visual acuity assessment of preschool children in the inner city area in Jakarta - Dian Estu Yulia; Yulinda Arty Laksmita; Julie Dewi Barliana; Laura Agnestasia Djunaedi; Lia Amanda; Hartono Gunardi (Paediatrica Indonesiana, 2022)
Background Visual acuity (VA) assessment is an important ocular examination to identify children with vision problems. Such early identification allows for early intervention to prevent childhood blindness. Objective To describe and compare visual acuity measurements in preschool children using two different visual acuity charts. Methods This cross-sectional study in children aged 36-60 months was done in a low-income area in the Central Jakarta District as a collaboration between Department of Ophthalmology and Department of Child Health, Universitas Indonesia Medical School/Dr. Cipto Mangunkusumo Hospital, Jakarta. All children underwent visual acuity examinations using Lea symbols and Tumbling E charts. The VA results from two charts were analyzed with Bland-Altman plot for limits of agreement. Statistical analyses were performed to determine the differences between vision charts. Results A total of 113 children enrolled, but only 38 children completed the examinations. The mean age of subjects was 50.5 (SD 6.4) months. Overall, subjects’ mean VA was 0.29 (SD 0.18) for Lea symbols and 0.37 (SD 0.14) for Tumbling E. The mean difference of VA between Lea symbols and Tumbling E was 0.07 (SD 0.22) logMAR units, with upper and lower limits of agreement at 0.36 and 0.51, respectively. There was no statistical difference in VA score using Lea symbols and Tumbling-E based on gender and age. Conclusion Most preschool children in our study have normal visual acuity. Lea symbols and Tumbling E chart are comparable and can be used to efficiently measure VA in preschool children.